"Del otro lado del espejo" (From the other side of the mirror) : Reflections about knowledge and society - Scaricabarozzi, Rossana (2015)
The intellectual role still has a powerful calling because the sacred fire of mankind has not been vanished: the action of discussing problematic issues. In fact, there is a minimum of cognitive grade, included in the most degraded analysis. This particular wandering of the spirit, or the exercise of intellect, may be defined as every process which can be used to record a human experience. The best metaphor to characterize it could be a travel. Even there is no a spatial movement from a place to another, but there is an imaginary movement, in which the wiser, without moving of this place, constructs a space from a present situation. He travels in a land imagined by the concepts, the abstractions which make him transcend his specific conditions (Ortiz “Taquigrafiando lo social”) (Taking the social in shorthand). This present article will be used as a pretext to think some of the paradoxes that show the intellectual task. We will expose below about the partial understanding of the cognizing subject and the social origin of cognition; then we will make some considerations with respect to the history and social production of the intellect; and, finally, we will refer to the language as a constructor of reality.